FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGELAPAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA TEMANGGUNG - Siti Fatimah; Dewi Kusuma Wardani (AKUNTANSI DEWANTARA, 2017)
This research aims to analyze the factors that influence of tax evasion. The independent variable in this research are tax fairness, taxation system, subjective norm, tax compliance, discrimination, quality of tax service, and probability of fraud detection while its dependent variable of tax evasion. The population in this research was an individual taxpayer listed in KPP Pratama Temanggung. The sample in this study is determined by sampling convinience method, the data collected with the distribution of questionnaires. The method of analysis used is multiple linear regression. Based on the results of the analysis indicate that the tax fairness and tax compliance has negative and significant on tax evasion, whiletaxation system, subjective norm, discrimination, quality of tax service, probability of fraud detection has no influenceon tax evasion.Keywords: Tax Fairness, Taxation System, Subjective Norm, Tax Compliance, Discrimination, Quality of Tax Service, and Probability of Fraud Detection.